Effect of different climatic environments on physiological characteristics of crossbred calves (Holandês X Gyr) - Mendes Araujo, Johnny Iglesias; Araujo, André Campêlo; Moreira Rodrigues, Hudson Taylor; Oliveira, Lianny Gomes; Barros Junior, Cicero Pereira; Lima Fonseca, Wéverton José; Monteiro Luz, Carlos Syllas; de Souza Júnior, Severino Cavalcante (Revista de Ciências Agroveterinárias, 2016)
The aim of this work was to verify the adaptability of crossbred calves (Holstein x Gyr) created in the field and in the facilities in Bom Jesus, PI. Six crossbred calves (Holstein x Gyr) were distributed in two treatments: T1= Field and T2= Facilities, with three animals in each, with 32 repeated measurements over time, totaling 192 observations (6 animals x 32 repetitions per animal) during the experimental period. The physiological characteristics, such as respiratory rate (RR), heart rate (HR), rectal temperature (RT), and the sweating rate (SR) were recorded. The meteorological variables were: air temperature (AT), relative humidity (RH), globe temperature index and humidity (BGT1 and BGT2), where BGT1 was inside the facilities and BGT2 in the open field. All weather variables showed significant differences (p<0.05) between shifts (morning and afternoon). It was found that RT and SR showed no significant difference (p>0.05). The RR was higher (p<0.05) for T1, with an average of 55.88 mov/min. There was a significant difference (p<0.05) between treatments for HR, with averages of 92.19 and 86.25 bat/min. for T1 and T2, respectively. According to the results it can be stated that the facilities for calves positively influenced the performance of heat loss, giving values closer to the comfort zone.